MODEL PENYELESAIAN PERSELISIHAN PARTAI POLITIK SECARA INTERNAL MAUPUN EKSTERNAL - Tri Cahya Indra Permana (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2016)
Political parties act stipulates that a political party dispute resolved internally by the Mahkamah Partai or other designation of that and externally resolved by the District Court and the Supreme Court. The dispute substance in Mahkamah Partai which is final and binding is about organization dispute, the other can be settled in District Court and the Supreme Court. In practice, that arrangement makes the decision apart from the sense of justice, legal certainty and utility. Therefore, these rules should be revised so that the regulation of PAW, violations of the rights of members of political parties, abuse of authority, financial liability, or an objection to the decision of political parties (including the decision not to decide on something) is final and binding through Mahkamah Partai decision. While the organization disputes can be submitted to the Constitutional Court for legal action.Keywords : political party dispute, Mahkamah Partai, Supreme Court,Constitutional Court